Konseling Realitas untuk Meningkatkan Resiliensi Siswa Korban Self injuiry - Nanditya, Bramana; Karneli, Yeni (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2021)
Victims of self-injury show the characteristics of injuring a limb with the intention of not killing to release emotional tension. This results in the client feeling the problem getting worse, withdrawing from his environment when there is a problem and taking it out by doing self-inquiry. Clients who have become aware begin to abandon these behaviors and develop the ability to remain calm in stressful conditions known as resilience. Self-inquiry which can lead to addiction when there is a serious problem needs to be given assistance efforts to increase the resilience of victims of self-inquiry. Integrating reality counseling is important because it relates to the client's 3R (righ, reality and responsibility) ability as well as the success identity and failure identity so that the client is able to increase his resilience. This qualitative research used a case study approach with the subject of one 15 year old victim of self-inquiry. Data were extracted by observation and interviews which were analyzed by data reduction, data presentation and drawing conclusions. The results showed that reality counseling can help increase the resilience of clients who are victims of self-inquiry. Korban self injury menunjukkan ciri melukai anggota tubuh dengan niat tidak membunuh untuk melepaskan ketegangan emosional. Hal ini mengakibatkan klien merasa permasalahannya bertambah berat, menarik diri dari lingkungannya ketika ada masalah dan melampiaskan dengan melakukan self injuiry. Klien yang telah sadar mulai meninggalkan perilaku tersebut dan mengembangkan kemampuan untuk tetap tenang dalam kondisi yang penuh tekanan yang dikenal dengan resiliensi. Self injuiry yang dapat menyebabkan ketagihan ketika ada masalah berat perlu diberikan upaya bantuan untuk meningkatkan resiliensi korban self injuiry. Pengintegrasian konseling realitas penting untuk dilakukan karena berhubungan dengan kemampuan 3R (righ, reality and respobsibilty) klien serta success identity dan failure identity agar klien mampu meningkatkan resiliensinya. Penelitian kualitatif ini menggunakan pendekatan studi kasus dengan subjek satu orang korban self injuiry usia 15 tahun. Data digali dengan observasi dan wawancara yang dianalisis dengan reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa konseling realitas dapat membantu meningkatkan resiliensi klien korban self injuiry.